2012
DOI: 10.3762/bjnano.3.31
|View full text |Cite
|
Sign up to set email alerts
|

Junction formation of Cu3BiS3 investigated by Kelvin probe force microscopy and surface photovoltage measurements

Abstract: SummaryRecently, the compound semiconductor Cu3BiS3 has been demonstrated to have a band gap of ~1.4 eV, well suited for photovoltaic energy harvesting. The preparation of polycrystalline thin films was successfully realized and now the junction formation to the n-type window needs to be developed. We present an investigation of the Cu3BiS3 absorber layer and the junction formation with CdS, ZnS and In2S3 buffer layers. Kelvin probe force microscopy shows the granular structure of the buffer layers with small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Peaks from carbon and oxygen are also present; not unexpected because of hydrocarbon contamination from exposure to atmosphere, which then subsequently reduced after cleaning. Sodium was also found, which did not decrease on cleaning, suggesting that the sodium has diffused through from the glass, as has been seen in similar materials 56 . Further discussion of the nature and effects of sodium with the corresponding spectra can be found in the SI.…”
Section: ×10supporting
confidence: 65%
“…Peaks from carbon and oxygen are also present; not unexpected because of hydrocarbon contamination from exposure to atmosphere, which then subsequently reduced after cleaning. Sodium was also found, which did not decrease on cleaning, suggesting that the sodium has diffused through from the glass, as has been seen in similar materials 56 . Further discussion of the nature and effects of sodium with the corresponding spectra can be found in the SI.…”
Section: ×10supporting
confidence: 65%
“…Numerous evaporation methods such as coevaporation, fast evaporation, thermal evaporation, and electron beam (EB) [21][22][23][24][25][26][27][28][29][30][31][32] have been employed for the deposition of Cu 3 BiS 3 thin films. Cu 3 BiS 3 thin films were deposited using two different attitudes:…”
Section: Vacuum-based Evaporation Deposition Methodsmentioning
confidence: 99%
“…Later on, Mesa et al [25] investigated the formation of ZnS, In 2 S 3 , and CdS buffer layers on Cu 3 BiS 3 for application as an absorber layer in solar cell. The Cu 3 BiS 3 and ZnS (thickness 200 nm) thin films were deposited by the co-evaporation techniques reported previously [23,26].…”
Section: Vacuum-based Evaporation Deposition Methodsmentioning
confidence: 99%
“…Further studies of the roles of heterojunctions and grain boundaries in Cu 3 BiS 3 are reported by Mesa, 116 who measured the surface electronic properties of NH 3 -cleaned Cu 3 BiS 3 films and also with overlayers of CdS, ZnS, and In 2 S 3 using Kelvin probe microscopy and surface photovoltage measurements. While the grain boundaries in the Cu 3 BiS 3 itself were found to be positively charged, a different behavior was seen when there was an over-layer of either CdS or In 2 S 3 (but not ZnS): the more positive work function at the positions of the grain boundaries in the underlying Cu 3 BiS 3 was taken as evidence that the over-layers changed the grain boundary charge state from negative to positive.…”
Section: Devices With Cu 3 Bismentioning
confidence: 99%